The Dogma of Christ and other essays on religion, psychology and culture - Fromm, Erich (New York : Holt, Rinehart and Winston, 1963)
Eight essays, some previously not published in English, by an eminent author and psychoanalyst.
The dogma of Christ -- The present human condition -- Sex and character -- Psychoanalysis -science or party line? -- The revolutionary character -- Medicine and the ethical problem of modern man -- On the limitations and dangers of psychology -- The prophetic concept of peace.
Keywords: Psychoanalysis and religion; Psychoanalysis and culture; Psychoanalysis